Practitioner's guide to data science - Lin, Hui (Quantitative researcher); Li, Ming (Research science manager) (Boca Raton : CRC Press, 2023)
"This book aims to increase the visibility of data science in real-world, which differs from what you learn from a typical textbook. Many aspects of day-to-day data science work are almost absent from conventional statistics, machine learning, and data science curriculum. Yet these activities account for a considerable share of the time and effort for data professionals in the industry. Based on industry experience, this book outlines real-world scenarios and discusses pitfalls that data science practitioners should avoid. It also covers the big data cloud platform and the art of data science, such as soft skills. The authors use R as the primary tool and provide code for both R and Python. This book is for readers who want to explore possible career paths and eventually become data scientists. This book comprehensively introduces various data science fields, soft and programming skills in data science projects, and potential career paths. Traditional data-related practitioners such as statisticians, business analysts, and data analysts will find this book helpful in expanding their skills for future data science careers. Undergraduate and graduate students from analytics-related areas will find this book beneficial to learn real-world data science applications. Non-mathematical readers will appreciate the reproducibility of the companion R and python codes"--
Soft skills for data scientists -- Introduction to the data -- Big data cloud platform -- Data pre-processing -- Data wrangling -- Model tuning strategy -- Measuring performance -- Regression models -- Regularization methods -- Tree-based methods -- Deep learning.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Statistics; COMPUTERS / Database Management / Data Mining; MATHEMATICS / Probability & Statistics / General; Big data; Data mining; Database management